Effects of Kangfuxinye on NF-κB and Inflammatory Cytokines in Gingival Crevicular Fluid of Patients with Orthodontic Gingivitis Caused by Orthodontic Treatment: Effects of Kangfuxinye on NF-κB and Inflammatory Cytokines - Li, Hui; Chen, Yan; Sun, Weiguo (Cellular and Molecular Biology, 2023)
Explore the Kangfuxinye effection on the expressions of nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) and inflammatory cytokines (IC) in the gingival crevicular fluid of patients with orthodontic gingivitis caused by orthodontic treatment. 98 patients with orthodontic gingivitis in Qingdao Stomatological Hospital caused by orthodontic treatment were divided into two groups, namely, the control treatment group and the Kangfuxinye treatment group. In this study, the expressions of those proteins and IC in gingival crevicular fluid before and after treatment were analyzed at first, and the correlations of the NF-κB p65 expression with IC were explored. Then the differences in the expressions of those proteins and IC and the efficacy between the control treatment group and the Kangfuxinye treatment group were analyzed. Compared with those before treatment, the expressions of NF-κB-related proteins and IC interleukin-1β (IL-1β), tumor necrosis factor-alpha (TNF-α) and vascular endothelial growth factor (VEGF)] were significantly decreased after treatment (p<0.05). After treatment, the expression of NF-κB p65 was positively correlated with IL-1β, TNF-α and VEGF, but negatively related to IL-4 and IL-10. In addition, compared with the control treatment, Kangfuxinye significantly reduced the expressions of those proteins and their messenger ribonucleic acids (mRNAs) (p<0.05), decreased the expressions of IL-1β, TNF-α and VEGF (p<0.05) but improved the total effective rate of treatment. Kangfuxinye can reduce the NF-κB expressions and IC in the gingival crevicular fluid of patients with orthodontic gingivitis caused by orthodontic treatment and enhance the efficacy.